Readability of English and Spanish forms of two adaptive behavior rating scales. Issue 5 (21st January 2021) - Wickerd, Garry; Tremblay, Sarah
Abstract: Adaptive behavior rating scales are widely used assessments that ask teachers and parents to rate how well students care for themselves, interact with others, and exhibit practical and academic skills. While adaptive rating scales have yielded reliable and valid results, it is unclear how the readability of the rating forms may impact the results, especially for parents who may have lower literacy levels. Using three readability indices—the Flesch Reading Ease for English, the Fernández Huerta for Spanish, and the Automated Reading Index for both English and Spanish—the readability of the English and Spanish parent/caregiver forms of the Vineland‐3 and ABAS‐3 was assessed. Results indicated that the reading grade level equivalent of the English and Spanish versions of the ABAS‐3 was on average greater than the recommended sixth grade level. In contrast, the readability of the Spanish and English versions of the Vineland‐3 was on average sixth grade level and below. Based on these results, when using parent/caregiver adaptive behavior rating forms, school psychologists should take precautions to ensure valid results by ascertaining parent/caregiver reading proficiency, providing additional explanations as permitted by the assessment protocols, and using alternative interview forms provided by publishers as needed.